Aggressive Angiomyxoma of Vulva - Panthi, Madhav; Kafle, Neeta; Pradhan, Tarun (Birat Journal of Health Sciences, 2021)
Aggressive angiomyxoma is a rare, slowly growing, and benign tumor of mesenchymal origin that usually occurs in the pelvis and perineum of young females. Steeper and Rosai in 1983, first described angiomyxoma. The term “aggressive” underlines the tumour’s locally infiltrative nature and high risk for local recurrence. The rate of relapse varies from 35% to 72%, however, it rarely metastasizes so it has an overall good prognosis. Diagnosis is mainly made on histopathology after surgical resection. The optimal treatment for aggressive angiomyxoma is wide local excision with tumor free margin. We here report a case of aggressive angiomyxoma in 22 years female who presented with mass on left labia majora.